Sistem Pendeteksi dan Monitoring Ruang Tahanan Menggunakan Sensor Getaran SW-420 dengan Komunikasi LAN - Handy Trias Permana (Jurnal Jaringan Telekomunikasi, 2019)
Securing detention rooms in Indonesia, using manual methods from humans to secure them. Officers check the detention room periodically. Several cases that occurred, such as the escape of prisoners from the Cawang Police and the Lhoksukhon Detention Center, the detainees broke into the bathroom wall using metal bars to be used as a media for breaking the walls. To prevent recurrence of cases, an early detection design is needed when there is a detention room indicated that it will be damaged by installing a vibration detection device on the wall. In this study, the SW-420 vibration sensor is used as a vibration detector when there is a wall to be broken into and several cameras installed in the corridor to visually monitor the occupants of the detention room. Vibration data will be sent to the detention room website via Arduino Uno, while the IpCamera will be connected to the router to display the video capture results on the website. For example, the bathroom plan for the detention room at the Gondanglegi Police Station that has been made, the sensor node is placed at the center point of the bathroom wall at a position of 60 cm which divides it into 2 parts. Arduino Uno will dynamically have IP when connected to the router using a Lan cable. Based on the experiment in the previous chapter, how to adjust the sensor sensitivity can be done by turning the sensitivity adjustment and adjusting the threshold on the website code.